Efektivitas Penggunaan Beberapa Jenis Ekoenzim Dalam Pengendalian Hama Ulat Bawang (Spodoptera Exigua) Pada Tanaman Bawang Merah (Allium Ascalonicum L) - Panjaitan, Delima (AGROSUSTAIN, 2025)
This study aims to determine the effect of concentration and variation of eco-enzyme, as well as the interaction between these two treatments, on the control of beet armyworm (Spodoptera exigua) pests in shallot plants (Allium ascolonicum L). The research was conducted in Sempakata Subdistrict, Medan Selayang District, Medan, at an altitude of 32–50 meters above sea level, from March to August 2024. A Randomized Complete Block Design (RCBD) was used, involving two factors. The first factor was eco-enzyme concentration (E), consisting of four levels: E1 = 5 cc/L water, E2 = 10 cc/L water, E3 = 15 cc/L water, and E4 = 20 cc/L water. The second factor was eco-enzyme variation (V), also consisting of four levels: V1 = Fruit-based eco-enzyme, V2 = Fruit-based eco-enzyme + Garlic, V3 = Fruit-based eco-enzyme + Lemongrass, and V4 = Fruit-based eco-enzyme + Tobacco. Data were analyzed using analysis of variance (ANOVA). The observed parameters included plant height, stem diameter, number of leaves, fresh bulb weight per sample, fresh bulb weight per plot, pest attacks, and pest attack intensity. Based on the results, eco-enzyme concentration had a significant effect on plant height at 4 weeks after planting (WAP), number of leaves at 2 WAP, pest attack intensity at 6 WAP, and a highly significant effect on pest attack intensity at 4 WAP. Eco-enzyme variation had a highly significant effect on plant height, stem diameter at 2 WAP, number of leaves, pest attacks at 4 WAP, and pest attack intensity at 4 and 6 WAP. It also had a significant effect on pest attacks at 2 and 6 WAP and pest attack intensity at 2 WAP. The interaction between eco-enzyme concentration and variation had a significant effect on plant height at 4 WAP and pest attack intensity at 4 WAP. The most effective eco-enzyme variation was the combination of fruit-based eco-enzyme and tobacco